Peningkatan Etos Kerja Guru Ditinjau Dari Gaya Kepemimpinan Kepala Sekolah - Irwan Suryadi (Universitas Pendidikan Indonesia, 2023)
The objective of this research is how the leadership of the principal can improve the work ethic of teachers in schools. The research method used a case study with a qualitative research approach. The results showed that the increase in the work ethicof teachers was evident from the leadership style adopted by the headmaster, so that a significant increase was obtained according to the vision and mission of the school. Work ethic is a mental attitude that contains values related to the morale of a teacher. The work of a teacher is currently understood as a professional, for that a teacher is required to have a work ethic that has positive work behavior at the level of awareness, confidence and high commitment in order to achieve the goals, vision and mission of the organization.